Soviet-Turkish Relations During the Cold War - Melkonyan, Kristine (History and Culture, 2023)
To recognize the nature of modern military-political events, it is necessary to study the processes that took place in the second half of the 20th century, since the Cold War and modern events have certain common features, the comparison and analysis of which can contribute to reasonable forecasts of political prospects. The study of Soviet-Turkish relations during the years of the Cold War is of particular importance, which not only allows us to understand the motivation for the foreign policy of the USSR and Turkey in the context of the formation of an international military-political confrontation, but also to consider the processes that influenced the nature of relations between the two countries and their development.The article discusses the features and stages of development of Soviet-Turkish relations during the Cold War. The 60s and 70s of the last century are especially mentioned, presenting the international processes that contributed to the improvement of Soviet-Turkish relations in those years.
Keywords: Cold War; Turkey; USSR; NATO; Soviet-Turkish relations; anti-Soviet policy; Cyprus crisis